First Asteroseismic Limits on the Nature of Dark Matter - Lopes, Ilidio (2014)
We report the first constraints on the properties of weakly interacting low-mass dark matter (DM) particles using asteroseismology. The additional energy transport mechanism due to accumulated asymmetric DM particles modifies the central temperature and density of low-mass stars and suppresses the convective core expected in 1.1-1.3 M ⊙ stars even for an environmental DM density as low as the expected in the solar neighborhood. An asteroseismic modeling of the stars KIC 8006161, HD 52265, and α Cen B revealed small frequency separations significantly deviated from the observations, leading to the exclusion of a region of the DM parameter space mass versus spin-dependent DM-proton scattering cross section comparable with present experimental constraints.